Real-world disproportionality analysis of cardiac failure associated with novel antineoplastic agents in breast cancer: a pharmacovigilance study - Li, Hui; Wu, YingJia; Guo, Qin; Guo, ChengShan; Liu, FangJie; Huo, LanQing (Frontiers in Immunology, 2025)
BackgroundSome antineoplastic agents have been implicated in cardiac failure (CF), but large-scale real-world data remain limited. This study aimed to assess disproportional reporting signals for CF associated with novel antineoplastic agents used in breast cancer treatment.MethodsA disproportionality analysis was conducted using individual case safety reports from the FDA Adverse Event Reporting System (FAERS, Jan 2004–Mar 2025), Canada Vigilance Adverse Reaction Database (CANADA, Jan 2004–Dec 2024), and Japanese Adverse Drug Event Report (JADER, Jan 2004–Oct 2024). Reports involving breast cancer patients treated with FDA-approved targeted agents were included. Reporting odds ratios (RORs), time-to-onset (TTO), and death proportion were evaluated by drug and class.ResultsA total of 8,565 CF cases were identified across the three databases. Trastuzumab exhibited consistently strong signals (FAERS: ROR 2.94; CANADA: 6.15; JADER: 7.05), with pertuzumab and everolimus showing variable significance. CDK4/6 inhibitors and immune checkpoint inhibitors (ICIs) demonstrated low or inverse RORs. Median TTO was longest for monoclonal antibodies, and shorter for ADCs and ICIs. Everolimus (20.1%), sacituzumab govitecan (22.6%), and atezolizumab (23.5%) showed the highest death proportions, while trastuzumab had a lower proportion (8.75%). HER2-targeted agents had higher reporting signal of CF than traditional chemotherapies.ConclusionThis study underscores drug-specific differences in CF risk among breast cancer therapies and highlights the importance of individualized cardiovascular risk assessment during treatment planning and monitoring.